Productive arts engagement at the Tokyo Fuji Art Museum and its health effects on the older Japanese population: results of a randomized controlled trial - Hayashi, Yoko; Matskiv, Jacqueline; Galery, Kevin; Beauchet, Olivier (Frontiers in Medicine, 2023)
Background This randomized controlled trial aims to compare changes in mental and physical health in older Japanese community-dwellers who participated in a productive art-based activity at the Tokyo Fuji Art Museum (intervention group) and in their counterparts, who did not participate in the intervention (control group). Methods A total of 73 older community-dwellers living in Tokyo participated in a single-blind RCT in two parallel groups (intervention group versus control group). The intervention was 2 h of productive art-based activities per week. The weekly sessions were carried out at the Tokyo Fuji Art Museum over a 12-week period. The control group did not participate in any productive art-based activity over the study period. Well-being, quality of life and frailty were assessed before the first, and after the last, art-based activity. These outcomes were assessed with the same schedule in both groups. Results The intervention group saw a significant improvement in their quality of life (p < 0.044) and mixed results on their physical health (i.e., decreased frailty status) when compared to the control group. The comparison of changes in frailty scores between M0 and M3 showed improvement in the intervention group (p = 0.014), but when adjusted for baseline characteristics by linear regressions, revealed only a trend (p = 0.070). No conclusive effect was shown with well-being. Interpretation This RCT showed mixed health effects of productive art engagement in older Japanese community-dwellers in Tokyo. Benefits were reported for quality of life and mixed effects were observed for frailty, while no significant effect was found for well-being. Clinical Trial Registration: Ethic committee of Shobi University, Tokyo (Japan), ref. A-2021-1; Clinical Trial Number NCT03679715.